Confusion of Horizons: Gadamer and the Christian logos - Zimmermann, Jens (Journal of beliefs and values, 2001)
This paper argues for Gadamer's indebtedness to logs Christology. Gadamer's language philosophy and hermeneutic experience both depend on theological insights gleaned mainly from St. Augustine and German Pietism. In Truth and Method , Gadamer uses Augustine's rewriting of Platonism to establish his language philosophy and employs the Pietist formula of application to describe the hermeneutical experience as word event. Gadamer's silence about these influences in his later works leave his interpreters and critics (such as Jürgen Habermas) puzzled about his seeming naïve trust in philosophical hermeneutics as a means to improve human interaction. This article tries to contribute to an understanding of Gadamer's hermeneutics by arguing that Gadamer's optimism in language and reason make sense when seen in the theological context from which crucial elements of his philosophy are derived.